Implementasi Program Literasi Digital Dalam Pengembangan Media Ajar Guru Madrasah Ibtidaiyah Di Kecamatan Klari: Penelitian - Gelar Gelora Mestika; Winda Dewi Listyasari; Muhamad Fadholi; Nurhattati Fuad (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to evaluate the implementation of a digital literacy program for Madrasah Ibtidaiyah teachers in Klari District, particularly in the development of digital based teaching media. This program was designed in response to the need to improve digital literacy among madrasah educators in line with developments in information technology. Post-test results indicate a significant improvement in teachers' understanding and skills in utilizing technology as a learning medium. The implications of this research suggest that the digital literacy program is effective in promoting the quality of learning at the Madrasah Ibtidaiyah level.